The role of lean body mass in predicting mortality in hemodialysis patients across different age groups - Ji-Eun Kim; Jinyeong Yi; Jae Ho Kim; Kipyo Kim; Joon Ho Song; Seoung Woo Lee; Seun Deuk Hwang (Scientific Reports)
Abstract Lean body mass (LBM) serves as an indicator of muscle mass in body composition. Recently, studies have revealed increased mortality rates in dialysis patients with low LBM. However, studies analyzing the impact of age on LBM and mortality in dialysis patients remain limited. This study analyzed data from 26,625 adult hemodialysis patients registered in the Korean Society of Nephrology (KSN) registry from 2001 to 2020. We used the lean body mass index (LBMI), standardized by the square of height, to normalize lean body mass. Patients were first categorized by age group (20–49, 50–69, and ≥ 70 years). Subsequently, patients were categorized into quartile groups based on their LBMI (≤ 15.55, 15.55 < LBMI ≤ 16.52, 16.52 < LBMI ≤ 17.59, and > 17.59). This study revealed that the lowest LBMI group (≤ 15.55) was associated with decreased survival across all age groups, with this trend being particularly prominent in the older age groups. Within the 20–49 age group, factors such as diabetes exhibited a notable influence on mortality rates among hemodialysis patients. In the age group over 50, a low LBMI (≤ 15.55) had a greater impact on mortality rates in hemodialysis patients than diabetes. Understanding the importance of LBM in older patients undergoing dialysis is crucial for improving their prognosis.